Sonographic Caval/Aorta Diameter And Inferior Vena Cava Collapsibility Indices For Assessment Of Preoperative Intravascular Volume Status In Elective Surgery Patients - Moktan, Sushila Lama; Sharma, Mona (Journal of Society of Surgeons of Nepal, 2024)
Introduction: The assessment of preoperative intravascular volume status is crucial for optimizing fluid management in patients undergoing elective surgery. Inaccurate volume status estimation can lead to complications related to hypovolemia or fluid overload. Traditional methods like central venous pressure monitoring are invasive and may not be readily available or accurate. The advances in non-invasive sonographic techniques offer an alternative approach. Two indices, the Caval/aorta diameter index (IVC/Ao) and inferior venacava collapsibility index (IVCCI), have shown a promise in evaluating intravascular volume status.Methods: This observational study included adult patients undergoing elective non-cardiac surgery. Ultrasonographic measurement of the IVC maximum and minimum diameter and aortic diameter were obtained before the  induction of anesthesia. The IVCCI and IVC/Ao index were then calculated. IVCCI of >50% and Caval/Ao index of